Optimal operation of tubular reactors for naphtha cracking by numerical simulation - Gao, G-Y.; Wang, M.; Ramshaw, C.; Li, X-G. (Wiley, 2011)
Process gas temperature profile and steam-to-hydrocarbon ratio in the feed have important impact on product yields and coking rate in tubular reactors for naphtha cracking. This study is to evaluate these effects quantitatively based on numerical simulation. Steady-state operation of the tubular reactor in an industrial thermal cracking furnace was first simulated in HYSYS with a molecular reaction scheme. Various case studies then investigate the influence of process gas temperature profile and inlet steam-to-hydrocarbon ratio so that the ethylene/propylene product yields and coking rate can be evaluated. Finally, steady-state optimization was applied to the operation of this industrial furnace. The optimal process temperature profile and the optimal inlet steam-to- naphtha ratio were found to maximize the operation profit. This study will provide significant guidance to process engineers in the ethylene industry.
Keywords: ethylene furnace; thermal cracking reaction; tubular reactor; process simulation; process optimization